From Environmental Stewardship To Environmental Holiness: The Evolution of Methodist Environmental Witness, with a Focus on Climate Change. - Stephens, Darryl W. (Journal of Religious Ethics, 2019)
The descriptive moment in ethical reflection is helpfully informed by a careful consideration of what religious bodies have said about moral issues such as climate change. As a case study, this article identifies and interprets primary documents of The United Methodist Church (UMC) and its predecessor institutions, providing a detailed examination of the historical development of this denomination's environmental witness statements. Methodism's long‐standing engagement with environmental ethics, out of which a concern for anthropogenic climate change incrementally emerged, includes significant institutional policies and practices. The history of Methodist environmental witness evidences a creative, faithful response by a religious denomination learning to grapple with the overwhelming problem of climate change. Describing and interpreting this history enables religious ethicists to engage Methodist environmental witness as they develop constructive models for addressing this problem.